Les puissances secondaires et l’influence des attributs relationnels : le cas du Canada et de sa politique extérieure - Munton, Donald (Études internationales, 1979)
Analyses et middle or « lesser » powers, unlike those of great and small powers, have not secured a distinctive place in the international politics literature and have generally not contributed to or borrowed from contemporary theoretical developments. The present study examines the foreign policy behavior of a lesser power (Canada) with an interrelated set of hypotheses drawn from theories explaining behavior as a function of the attributes of targets and actors. The four « relational » attributes employed here are status, salience, similarity, and proximity. Quantitative measures for these relational factors and for five categories of Canadian behavior across 51 (Canada to x) dyads are developed with particular attention being paid to questions of empirical-theoretical fit. Correlational analysis reveals many of the relational attributes and indicators explain a significant amount of variation in the behavior measures. Greater status, salience and proximity generally lead to more frequent Canadian activity. Status differences are particularly strongly related to all five types of dyadic behavior. Similarity appears a less influential factor. A further partial correlation analysis suggests that for Canada the relational attributes are interrelated with each other and with behavior in a patterned way. Greater proximity leads to increased salience, as do greater status and similarity. In turn, greater salience, status and similarity all lead to more frequent behavior of most types. These results tend to support some and refute other general hypotheses about target-actor attributes and behavior, and perhaps suggest some particular features of lesser power activity.